A ‐1573T>C SNP within the human TRAIL promoter determines TRAIL expression and HCC tumor progression. (31st August 2016) - Piras‐Straub, Katja; Khairzada, Khaleda; Kocabayoglu, Peri; Paul, Andreas; Gerken, Guido; Herzer, Kerstin
Abstract: The cytokine tumor necrosis factor (TNF)‐related apoptosis‐inducing ligand (TRAIL) induces apoptosis in liver cancer cells but not in normal liver cells. Therefore, TRAIL got credited to play a role in hepatocellular carcinoma (HCC) development and progression. Impaired expression of TRAIL in HCC cells and sequence variations in the TRAIL promoter may facilitate development, growth, and spread . The TRAIL promoter was sequenced from liver tissue of 93 patients undergoing partial liver resection (PRT) or liver transplantation (LT) for HCC. TRAIL mRNA expression was investigated by quantitative real‐time PCR. A variant ‐1573T>C (single‐nucleotide polymorphism; C, cytosine) SNP was characterized by electron mobility shift assay and supershift assays. Functionality of the ‐1573T>C SNP was analyzed in reporter gene assays and cell migration assays. In approximately 30% of HCC samples, a loss‐of‐function shift of the binding pattern due to a ‐1573T>C SNP was found within the human TRAIL promoter. Correlation analysis revealed significantly lower TRAIL expression in HCC samples with the ‐1573C sequence ( P ≤ 0.05). Reporter gene assays revealed significantly reduced inducibility of the TRAIL promoter due to the ‐1573C sequence. The variant ‐1573C sequence impaired not only binding of transcription factors but also expression of TRAIL. Interestingly, this impairment resulted in enhanced migration activity and colony formation of the liver tumor cells. Our findings suggest that loss of function of the human TRAIL promoter due to the ‐1573T>C SNP leads to reduced expression and impaired inducibility of TRAIL, with the consequence of enhanced growth and migration of tumor cells, ultimately resulting in the progression of the HCC. Abstract : We investigated sequences of the TRAIL promoter from a large number of human hepatocellular carcinoma (HCCs), observing a SNP (single‐nucleotide polymorphism) within a GATA‐1‐binding site which is related to a loss‐of‐function of the corresponding GATA‐1 site, resulting in a reduced TRAIL expression and increased tumor cell migration. This is the first report on a SNP in the TRAIL promoter segment with implications for the regulation of TRAIL, and thus, with predictive value for HCC development.